The Human Capital Study 2002–04: Tracking, data collection, coverage, and attrition - Grajeda, Rubén (2005)
Between 2002 and 2004, the Institute of Nutrition of Central America and Panama (INCAP), in collaboration with Emory University, the International Food Policy Research Institute (IFPRI), and the University of Pennsylvania, re-surveyed young Guatemalan adults who had, as children, been participants in a nutrition supplementation trial conducted by INCAP between 1969 and 1977. This “Human Capital Study 2002–04” complements and extends data obtained in previous studies by collecting new information on measures of physical health and well-being, schooling and cognitive ability, wealth, consumption and economic productivity, and marriage and fertility histories. This paper describes the study domains and data collection procedures. Among 2,393 members of the original sample, 1,856 (77%) were targets for enrollment. Response rates varied by gender, current place of residence, and domain of data collection, with 80% of males and 89% of females completing at least one data collection instrument. Attrition was not random and appears to be associated with a number of initial characteristics of individuals and their households that should be controlled for in future analyses. We conclude that data collection was successful and data quality is high, facilitating the successful undertaking of our planned investigation of important study hypotheses.